Bitcoins, Blockchain und Distributed Ledgers: Funktionsweise, Marktentwicklungen und Zukunftsperspektiven - Volker Brühl (Wirtschaftsdienst, 2017)
Virtuelle Währungen wie Bitcoins geraten zunehmend in den Blickpunkt des öffentlichen Interesses. Sie funktionieren auf Basis der Blockchain- bzw. Distributed-Ledger-Technologie. Volker Brühl erläutert ihre Funktionsweise und zeigt auf, dass diese Technologien nicht nur den Finanzsektor revolutionieren können. – – Cryptocurrencies such as bitcoin were invented to facilitate instant payment services without the need for a central bank or financial intermediaries executing payments. Using cryptographic functions, any user of the bitcoin system can transfer units of the virtual currency globally on an anonymous basis. However, fi nancial supervisory authorities are about to increase regulation of virtual currencies due to concerns that the anonymous character of the system facilitates money laundering and the financing of illegal transactions. Nevertheless, the underlying blockchain technology, or in broader terms the distributed ledger technology, may revolutionise several industries. This paper illustrates the functioning and recent market developments in the bitcoin industry as well as the disruptive potential of the underlying technologies.
Keywords: G10; G20; G29; 330